Answer:
Answer C
Step-by-step explanation:
The rules of logarithmic functions require the two log functions to have the same base. If they do not have the same base, you cannot apply any of the rules.
Answer:
y=2x^2 + 2x - 3 x -2 -1 0 1 2
Step By Step Explanation:
The values can be find by plugging the x values in the equation which gives us the y value ,
x -2 -1 0 1 2
y 1 -3 -3 1 9
(b) Plot the points on the graph and join by a smooth curve.
(c) The line y=1 will be passing through 1 and parallel to x-axis.
(d) solve 2x^2 + 2x - 3 = 1
Subtract 1 from both the sides ,
2x^2 + 2x - 2 = 0
Factoring out the 2 from the equation ,
2(x^2 + x - 1) = 0
x^2 + x - 1 = 0
Apply the quadratic formula
x=(-1-sqrt(5))/2 and x = (-1+sqrt(5))/5
Answer:
5
Step-by-step explanation:
Because if you divide them all you see that in 5 you don't get a whole number